Allometry of native Mexican Jatropha curcas L. seeds - Valdés-Rodríguez Ofelia Andrea; Sánchez-Sánchez Odilón; Pérez-Vázquez Arturo; Zavala del Angel Iván (Revista Mexicana de Ciencias Agrícolas, 2018)
This work presents a comparative morphological study of four Mexican sources. Three non-toxic, non-commercial sources from the state of Veracruz (Papantla, Medellín and Alvarado) and one toxic provenance belonging to a commercial plantation in the state of Colima (Tecomán), were analyzed over two years. An average of 480 seeds per provenance, per year were characterized by estimating their phorbol-ester contents, determining their sizes and weights, correlating data between kernel weight versus total seed weight, documenting their agronomic conditions and comparing them with other Mexican sources. Significant differences were found in seed morphology per provenance (p< 0.05). Larger and heavier seeds were found in Papantla (760 mg in average) and Tecoman (746 mg), where environmental conditions were better than in Medellin (651 mg) and Alvarado (686 mg). Seed length was the parameter that had the highest positive correlation with weight (p> 0.86) and seed volume had the lowest coefficient of variation (CV< 4.5%) for all sources. Apart from genetic factors, weight and size could also be related to crop management practices and soil fertility, since the largest and heaviest seeds came from the more fertile soils or fertilized and irrigated plantations, while the smallest and lighter seeds came from semi-wild sources located in sandy soils.